Protected cultivation of vegetables in Sub-Saharan Africa: Scope and impacts - (:unkn) unknown (My University, 2020)
This chapter focuses on protected cultivation (PC), defined as the protection of crops against adverse climatic and biological factors using physical means. As natural resources become scarcer, farm inputs become more expensive and consumers more attentive to the sanitary and nutritious aspects of food produced, PC has become one promising yet improvable way to address these challenges. As the global demand for high value crops, such as vegetables, increases, PC appears an opportunity for farmers to increase their income, improve their working conditions and secure their production, thereby attracting youth to enter the crucial but aging farming sector. In Sub-Saharan Africa, farmers constantly face the threat of losing their crops due to pests, diseases or harsh climatic conditions, with no insurance to cover their loss. A case study, comparing PC of tomatoes in Benin and Tanzania, showed that PC is profitable despite high initial investments, provided there is a market for high quality produce. Favourable policies, farmers' training and agronomic research are prerequisites to the adoption and development of PC technologies and techniques in Sub-Saharan Africa. PC has the potential to enhance bioeconomy in the region and at the same time achieve some of the SDGs.
Keywords: African Research